Role of the ISKpn element in mediating mgrB gene mutations in ST11 hypervirulent colistin-resistant Klebsiella pneumoniae - Zhu, Lanlan; Li, Ping; Zhang, Guangyi; He, Zhiyong; Tao, Xingyu; Ji, Yicheng; Yang, Wenjing; Zhu, Xiaofang; Luo, Wanying; Liao, Wenjian; Chen, Chuanhui; Liu, Yang; et al. (Frontiers in Microbiology, 2023)
Background Colistin has emerged as a last-resort therapeutic against antibiotic-resistant bacterial infections, particularly those attributed to carbapenem-resistant Enterobacteriaceae (CRE) like CRKP. Yet, alarmingly, approximately 45% of multidrug-resistant Klebsiella pneumoniae strains now manifest resistance to colistin. Through our study, we discerned that the synergy between carbapenemase and IS elements amplifies resistance in Klebsiella pneumoniae, thereby narrowing the existing therapeutic avenues. This underscores the instrumental role of IS elements in enhancing colistin resistance through mgrB disruption. Methods From 2021 to 2023, 127 colistin-resistant Klebsiella pneumoniae isolates underwent meticulous examination. We embarked on an exhaustive genetic probe, targeting genes associated with both plasmid-mediated mobile resistance-encompassing blaKPC, blaNDM, blaIMP, blaVIM, blaOXA-48-like, and mcr-1 to mcr-8-and chromosome-mediated resistance systems, including PhoP/Q, PmrA/B, and mgrB. PCR amplification revealed the presence of virulence-associated genes from the pLVPK plasmid, such as rmpA, rmpA2, iucA, iroB, and peg344. mgrB sequencing was delegated to Sangon Biotech, Shanghai, and the sequences procured were validated using BLAST. Our search for IS elements was navigated through the IS finder portal. Phenotypically, we harnessed broth microdilution (BMD) to ascertain the MICs of colistin. To sketch the clonal lineage of mgrB-mutated CoR-Kp isolates, sophisticated methodologies like MLST and PFGE were deployed. S1-PFGE unraveled the intrinsic plasmids in these isolates. Our battery of virulence assessment techniques ranged from the string test and capsular serotyping to the serum killing assay and the Galleria mellonella larval infection model. Results Among the 127 analyzed isolates, 20 showed an enlarged mgrB PCR amplicon compared to wild-type strains. These emerged over a three-year period: three in 2021, thirteen in 2022, and four in 2023. Antimicrobial susceptibility tests revealed that these isolates consistently resisted several drugs, notably TCC, TZP, CAZ, and COL. Additionally, 85% resisted both DOX and TOB. The MICs for colistin across these strains ranged between 16 to 64 mg/L, with a median of 40 mg/L. From a genetic perspective, MLST unanimously categorized these mgrB-mutated CoR-hvKp isolates as ST11. PFGE further delineated them into six distinct clusters, with clusters A and D being predominant. This distribution suggests potential horizontal and clonal genetic transmission. Intriguingly, every mgrB-mutated CoR-hvKP isolate possessed at least two virulence genes akin to the pLVPK-like virulence plasmid, with iroB and rmpA2 standing out. Their virulence was empirically validated both in vitro and in vivo. A pivotal discovery was the identification of three distinct insertion sequence (IS) elements within or near the mgrB gene. These were:ISKpn26 in eleven isolates, mainly in cluster A, with various insertion sites including +74, +125, and an upstream −35.ISKpn14 in four isolates with insertions at +93, −35, and two upstream at −60.IS903B present in five isolates, marking positions like +74, +125, +116, and −35 in the promoter region. These diverse insertions, spanning six unique locations in or near the mgrB gene, underscore its remarkable adaptability. Conclusion Our exploration spotlights the ISKpn element’s paramount role in fostering mgrB gene mutations in ST11 hypervirulent colistin-resistant Klebsiella pneumoniae. Employing MLST and PFGE, we unearthed two primary genetic conduits: clonal and horizontal. A striking observation was the ubiquitous presence of the KPC carbapenemase gene in all the evaluated ST11 hypervirulent colistin-resistant Klebsiella pneumoniae strains, with a majority also harboring the NDM gene. The myriad mgrB gene insertion locales accentuate its flexibility and the overarching influence of IS elements, notably the pervasive IS5-like variants ISKpn26 and IS903B. Our revelations illuminate the escalating role of IS elements in antibiotic resistance within ST11 hypervirulent colistin-resistant Klebsiella pneumoniae, advocating for innovative interventions to counteract these burgeoning resistance paradigms given their profound ramifications for prevailing treatment modalities.